Sungit - Liza Flores (Quezon City : Adarna House, Inc., 2020)
Ayan na ang sungit. Magpapatalo kaya ako sa sungit? (From the back cover of the book).
Keywords: Reader's(Primary).; Filipino language -- Phonetics; Children's stories